Influence of cancer cachexia on drug liver metabolism and renal elimination in rats. Issue 1 (March 2015) - Cvan Trobec, Katja; Kerec Kos, Mojca; Trontelj, Jurij; Grabnar, Iztok; Tschirner, Anika; Palus, Sandra; Anker, Stefan D.; Springer, Jochen; Lainscak, Mitja
Abstract: Background: Body wasting and cachexia change body composition and organ function, with effects on drug pharmacokinetics. The aim of this study was to investigate how cancer and cancer cachexia modify liver metabolism and renal drug elimination in rats. Methods: Nine male Wistar‐Han rats received a single oral dose of midazolam and propranolol (markers of hepatic metabolism), and 10 rats received single intravenous dose of iohexol, a marker of glomerular filtration rate. After drug delivery, multiple dried blood samples were obtained within 2 h post‐dose to evaluate drug pharmacokinetic profiles. After baseline sampling (D0), rats were injected with tumour cells. Drug application and blood sampling were repeated when rats developed tumours (Day 5—D5), and when rats were severely cachectic (Day 10—D10). Clearance (CL) and volume of distribution (Vd) of drugs were assessed with non‐linear mixed effects modelling. Weight and body composition were measured on D0 and D10 and were related to pharmacokinetic parameters. Results: All three drugs showed non‐significant trend towards increased CL and Vd on D5. On D10, midazolam and propranolol CL and midazolam Vd significantly decreased from baseline (−80.5%, −79.8%, and −72.0%, respectively, P  < 0.05 for all). Iohexol CL decreased by 29.8% from baseline value on D10, which was related to body weight loss (Pearson's r  = 0.837, P  = 0.019). Conclusions: Hepatic metabolism and renal drug elimination are significantly reduced in cachexia, which could increase risk of dose‐related adverse events.